A novel nutritional risk score and prognosis of oral cancer patients: A prospective study. (23rd December 2020) - Chen, Qing; Fan, Yi; Li, Yanni; Wang, Jing; Chen, Lin; Lin, Jing; Chen, Fa; Wang, Jing; Qiu, Yu; Shi, Bin; Pan, Lizhen; Lin, Lisong; et al.
Abstract: Objectives: To evaluate the prognostic performance of a novel nutritional risk score based on serum iron, hemoglobin, and body mass index (BMI) in oral cancer patients, and to predict the response to chemotherapy in patients with different nutritional status. Methods: X‐tile analysis was performed to determine the optimal cutoff values of serum iron, hemoglobin, and BMI. A nutritional risk score was established by using the HR values of serum iron, hemoglobin, and BMI. Kaplan–Meier curve and multivariable Cox proportional hazards models were used to evaluate the prognostic value of the nutritional risk score in overall survival (OS) and oral cancer‐specific survival (OCSS). Results: Serum iron, hemoglobin, and body mass index were all inversely related to the prognosis of oral cancer. The adjusted HR of serum iron, hemoglobin, and BMI were 1.562, 1.886, and 1.465 for OS, and 1.653, 1.865, and 1.443 for OCSS. Patients with higher nutritional risk score had a poorer OS and OCSS. Additionally, chemotherapy was only associated with improved OCSS in patients with the lowest nutritional risk score, but not in patients with higher one. Conclusions: Nutritional risk score is of prognostic value in oral cancer patients. Favorable response to chemotherapy may only be observed in well‐nourished oral cancer patients with lower nutritional risk score.